1975
DOI: 10.1159/000208045
|View full text |Cite
|
Sign up to set email alerts
|

Erythroblastic Islands and Ineffective Erythropoiesis in Acute Myeloid Leukaemia

Abstract: The erythropoietic part of the bone marrow has been morphologically analysed in 34 untreated, anaemic patients with acute myeloid leukaemia and in 17 healthy controls. In the patients with leukaemia the percentage of basophilic erythroblasts was abnormally high and elevated mitotic indices of the erythroblasts were recorded. The accumulation of basophilic erythroblasts and a high frequency of megaloblastoid changes of the cells may indicate ineffective erythropoiesis. A threefold increase of ‘erythroblastic is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…It has been suggested that the abundance of erythroblastic islands in acute myeloid leukaemias with a high frequency of megaloblastoid erythroblasts may be signs of ineffective erythropoiesis [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the abundance of erythroblastic islands in acute myeloid leukaemias with a high frequency of megaloblastoid erythroblasts may be signs of ineffective erythropoiesis [10].…”
mentioning
confidence: 99%
“…Special interest was devoted to the abundance of erythroblastic islands in the bone marrow, spleen and liver of the CML patients. It has previously been suggested that the presence of such formations may indicate phagocytosis of erythroblasts into reticulum cells [9,10], thus being a sign of increased death rate of abnormal erythroblasts.…”
mentioning
confidence: 99%
“…Nowadays cytogenetic, kinetic and morphologic investigations confirm this. Thus cytophotometric-autoradiographic studies in acute leukaemias have shown a marked proliferation disturbance which was almost limited to the early polychromatic erythroblasts representing a nonproliferative population (Queisser et a1 1973, 1975, Mitrou et a1 1975. A maturation arrest of the polychromatic cells results in a shift to the left within the erythropoietic pool.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous reports on the MI of the erythroblasts do not coincide well. Thus subnormal MI have been reported in acute erythroleukaemia (AEL) (Tsuchiya & Maekawa 1973) but also significantly elevated indices (Sjogren 1975). In acute myeloblastic leukaemia (AML) Huber et al (1971) found low MI and Sjogren (1975) values above those of the normals.…”
mentioning
confidence: 96%
See 1 more Smart Citation